A német kisebbség helyzete a Horthy-korszakban - Szávai, Ferenc (Közép-Európai Közlemények, 2015)
The multinational Austro-Hungarian Monarchy succeeded in unifying its nationalities in economic terms for a long period; Hungary’s development showed outstanding results in this respect. The proportion of Hungarians, however, did not even reach 50% in this era. The situation changed considerably after World War I. The state area became more homogenous, its largest minority became the Germans in Hungary. This study aims to evaluate their situation in the Horthy era, in terms of two aspects: regarding, on the one hand, a new wave of name Magyarizing, on the other hand, their independent economic activities. At the same time, the German state saw significant economic opportunities in the German population in Hungary.